THE INFLUENCE OF SOIL COVER ON LAKES IN NORTHERN ESTONIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1999)
During the summers of 1997-98, in a pine-forested sloping watershed, soil water from calcareous and sandy soil horizons was collected on nine occasions. In total 8 lysimeters were used. The amount of water percolating through sandy test site was up to three times smaller than that through calcareous test site. The influence of soil cover on the percolating water is also significant. The sandy site is able to produce even more diluted water than that originally coming from precipitation. Concentrations of TOC are varying more than the conductivity values. The concentration of TOC on the calcareous site was 2... 2,5 times higher than that on the sandy site. The total emission of TOC from the transitional humus-rich test site could be higher by up to 20 times as compared with sandy site.